Unexplained Infertility: Comparison of Efficacy of Letrozole and Clomiphene Citrate - Shahida Magsi, Shaista Lashari, Rukhsana Shaikh, Inayat Magsi, Sonia Gul Qureshi, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Infertility is always been considered as social issue because of its impact on individuals as well as on families. Unexplained infertility defined as inability of a couple to conceive after one year of unprotected intercourse even in the absence of any specific reason for it. Aim: To compare the efficacy of letrozole and clomiphene citrate among patients presenting with unexplained infertility Study design: Prospective observational study. Place and duration of study: Department of Obstetrics & Gynecology, Sheikh Zayed Women Hospital Larkana from 1st January 2020 to 31st December 2020. Methodology: Three hundred and thirty six women having unexplained infertility were randomly allocated into two groups. One hundred and sixty eight patients in group A were given letrozole 2.5mg and 168 women in group B received clomiphene citrate 50mg for three months with successive increase in dose up to 3 cycles, if not conceived in first cycle. They were assessed for pregnancy after 4, 8 and 12 weeks of treatment. Results: The average age of the patients was 27.01±2.53 years. Efficacy of letrozole was significantly high as compare to clomiphene citrate [82.1%vs.62.5%;p=0.0005]. Conclusion: The efficacy of letrozole was significantly high as compared to clomiphene citrate. Letrozole is a better alternative for ovulation induction in anovulatory women because it has high pregnancy rates with shorter time to pregnancy and chances of multiple pregnancies are less because of high monofollicular growth.